2020
DOI: 10.1007/s40265-020-01376-y
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Exposure to Biologics in Inflammatory Autoimmune Diseases: A Systematic Review

Abstract: Background Inflammatory autoimmune diseases are chronic diseases that often affect women of childbearing age. Therefore, detailed knowledge of the safety profile of medications used for management of inflammatory autoimmune diseases during pregnancy is important. However, in many cases the potential harmful effects of medications (especially biologics) during pregnancy (and lactation) on mother and child have not been fully identified. Objective Our aim was to update the data on the occurrence of miscarriages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 142 publications
(130 reference statements)
2
10
0
2
Order By: Relevance
“…Overall, our findings agree with these other recent systematic reviews [129,130] and have not identified any evidence of an increased risk of APO compared to the general population, when considering either non-TNFI and tsDMARDs as a whole, by mode of inhibition or as individual drugs. The increasing body of evidence from ours and other recent systematic reviews should be viewed as useful adjuncts to existing guidelines/recommendations [6][7][8][9], particularly where either conditional or no recommendations could be made due to lack of evidence.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Overall, our findings agree with these other recent systematic reviews [129,130] and have not identified any evidence of an increased risk of APO compared to the general population, when considering either non-TNFI and tsDMARDs as a whole, by mode of inhibition or as individual drugs. The increasing body of evidence from ours and other recent systematic reviews should be viewed as useful adjuncts to existing guidelines/recommendations [6][7][8][9], particularly where either conditional or no recommendations could be made due to lack of evidence.…”
Section: Discussionsupporting
confidence: 93%
“…Tsao et al [129] conducted a meta-analysis of 24 studies comparing pregnancy outcomes in biologic and non-biologic exposed pregnancies and did not find any association between biologic exposure and congenital malformation, pre-term birth or low birth weight. Ghalandari et al [130] systematically reviewed 143 studies, primarily considered data on miscarriages and congenital malformations from biologic pregnancy exposures, and did not report any major safety issues. There are important methodological differences between these studies and our own, such that each yields distinct and useful information upon biologic use in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ) (ACR 2020: „conditionally recommended“) [ 4 ]. Dabei ist die Datenlage zu jedem einzelnen Biologikum limitiert oder nicht existent [ 42 , 43 ]. Jedoch leiten sich diese Empfehlungen von der Pharmakokinetik der monoklonalen Antikörper ab.…”
Section: Biologika In Der Stillzeitunclassified
“…Что касается безопасности иФНОα при гестации у женщин c иммуновоспалительными заболеваниями, то, по данным систематического обзора проспективных и ретроспективных исследований, выполненных в 2015-2019 гг. [12], на фоне терапии АДА, ЭТЦ, ЦЗП частота спонтанных абортов (0,4-17,4%), преждевременных родов (3,2-11,5%), врожденных пороков развития (1,9-6,2%) не отличались от общепопуляционной, что подтверждает полученные ранее сведения о профиле безопасности иФНО; серьезные инфекции были зафиксированы у 0-7,9% младенцев. У детей, матери которых получали ИНФ во время беременности, серьезные инфекции встречались в среднем в 18,2% случаев.…”
unclassified